USULAN STRATEGI BISNIS PADA MASA PANDEMI COVID-19 DI PT XYZ DENGAN BUSINESS MODEL CANVAS - Hambali Muslimin (2021)
The excellent growth of the restaurant industry had to be hampered by the Covid-19 pandemic. This forces restaurant entrepreneurs including PT XYZ which is a restaurant in Jambi city to adapt in order to survive. This study aims to provide a business model proposal during the Covid-19 pandemic for PT XYZ by using the Business Model Canvas. The supporting methods used to get the right proposal are SERVQUAL and SWOT. From the results of the study, there were several focuses that PT XYZ could apply to its business model during the Covid-19 pandemic. The focus is improving service quality by educating employees, increasing promotions on the internet, improving delivery services and implementing strict health protocols in accordance with government regulations.